Recent Advances in Targeting CD8 T-Cell Immunity for More Effective Cancer Immunotherapy - Durgeau, Aurélie; Virk, Yasemin; Corgnac, Stéphanie; Mami-Chouaib, Fathia (Frontiers in Immunology, 2018)
Recent advances in cancer treatment have emerged from new immunotherapies targeting T-cell inhibitory receptors, including CTLA-4 and PD-1. In this context, anti-CTLA-4 and anti-PD-1 monoclonal antibodies (mAb) have demonstrated survival benefits in numerous cancers, including melanoma and non-small-cell lung carcinoma (NSCLC). PD-1-expressing CD8+ T lymphocytes appear to play a major role in the response to these immune checkpoint inhibitors (ICI). Cytotoxic T lymphocytes (CTL) eliminate malignant cells through recognition by the T-cell receptor (TCR) of specific antigenic peptides presented on the surface of cancer cells by major histocompatibility complex class I (MHC-I)/beta-2-microglobulin (beta2m) complexes, and through killing of target cells, mainly by releasing the content of secretory lysosomes containing perforin and granzyme B. T-cell adhesion molecules and, in particular, lymphocyte-function-associated antigen-1 (LFA-1) and CD103 integrins, and their cognate ligands, respectively, intercellular adhesion molecule 1 (ICAM-1) and E-cadherin, on target cells, are involved in strengthening the interaction between CTL and tumor cells. Tumor-specific CTL have been isolated from tumor-infiltrating lymphocytes (TIL) and peripheral blood lymphocytes (PBL) of patients with varied cancers. TCRbeta-chain gene usage indicated that CTL identified in vitro selectively expanded in vivo at the tumor site compared to autologous PBL. Moreover, functional studies indicated that these CTL mediate human leukocyte antigen class I (HLA-I)-restricted cytotoxic activity toward autologous tumor cells. Several of them recognize truly tumor-specific antigens (TSA) encoded by mutated genes, also known as neoantigens, which likely play a key role in anti-tumor CD8 T-cell immunity. Accordingly, it has been shown that the presence of T lymphocytes directed toward tumor neoantigens is associated with patient response to immunotherapies, including ICI, adoptive cell transfer (ACT) and the dendritic cell-(DC)-based vaccine. These tumor-specific mutation-derived antigens open up new perspectives for development of effective second-generation therapeutic cancer vaccines.